ANTIBACTERIAL AND ANTIBIOFILM POTENTIAL OF ETHANOLIC EXTRACT FROM BINTARO FLOWER (Cerbera odollam) AGAINST Staphylococcus aureus ATCC 6538 - Dwi Rahma Suci Lestari; Lisa Soegianto; Liliek S. Hermanu (UNEJ e-Proceeding)
Staphylococcus aureus are examples of Grampositivebacteria that can cause infection.Treatment of infection with antibiotic synthesiscan bring its own problems, namely the resistanceof bacteria to antibiotics. Resistant bacteria is abacterial pathogen that is capable of formingbiofilms on living beings. Traditional medicine canbe another alternative in the treatment ofinfections. Natural compounds that have thepotential as an antibacterial commonly containsteroids, tannins, polyphenols, flavonoids1),alkaloids, saponins2).Some studies related to the use as an antibacterialBintaro explained that the mangrove plant thatbelongs to the family Apocynaceae is grown widelyin the southern coast of East Asia and the IndianOcean has antibacterial activity3).This study was conducted to determine theantibacterial activity and antibiofilm of ethanolicextract from Cerbera odollam flower againstStaphylococcus aureus.